Modal analysis of notched beam - Naeem, Zulkifle (2010)
Modal analysis is the study of the dynamic properties of structures under vibrational excitation. The purpose of this study is to determine the dynamic behavior of notched beam for various distances and notch size and their effect on natural frequency. In this project, six beams are used to perform in simulation and experimental hammer test. Finite Element Analysis (FEA) comprise of a computer model of a material that is stressed and analyzed for specific results. ALGOR Fempro is used to analyze the model that build in SOLIDWORK. After modeling the beam with dimension as desired in Solidwork software, CAE Analysis or ALGOR Fempro used to simulate the beam to obtain natural frequency. The finite element model of the components was analyzed using the Natural Frequency (modal) approaches. Finally, the natural frequency obtain from the result of analysis are known as simulation result. In the experimental hammer test, natural frequencies are obtained from Frequency Response Function (FRF) graph using PULSE Labshop Software. Relationship between results of experimental and simulation showed the effect of notch on beam with both distance and depth. It is shown that the natural frequency is decreasing with the increasing of distance of notch and depth of notch on beams.